Chlorinated and nonchlorinated-volatile organic compounds (VOCs) in drinking water of peninsular Malaysia - Md. Pauzi Abdullah,; Soh, Shiau Chian (Universiti Kebangsaan Malaysia, 2011)
A survey undertaken in Peninsular Malaysia has shown that volatile organic compounds (VOCs), both chlorinated and non-chlorinated, are present in selected drinking water samples. In this study, analyses of VOCs were performed by means of solid phase microextraction (SPME) with a 100 μm polydimethylsiloxane (PDMS) fibre followed by gas chromatography - mass spectrometry detector (GC-MSD). Samples from different points of the distribution system networks were taken and analysed for 54 VOCs of different chemical families. The results of the study indicated that chloroform constituted the major portion of the VOCs in all samples analysed. In addition to trihalomethanes (THMs), other abundant compounds detected were cis and trans-1,2-dichloroethylene, trichloroethylene, 1,2-dibromoethane, benzene, toluene, ethylbenzene, chlorobenzene, 1,4-dichlorobenzene and 1,2-dichlorobenzene. However, the measured concentrations did not exceed the National Guideline for Drinking Water Quality 2000 in any case. No clear relationship between the status of development of a state in Malaysia to the levels and types of VOCs detected in its drinking water was noted. Nevertheless, the finding of anthropogenic chemicals, even at low concentrations, gave credibility to the viewpoint that improper development and disposal practices threatened the purity of the drinking water.